A influência dos ativos intangíveis na análise de risco de crédito de empresas de base tecnológica - Honorato, Hermes Guimarães (2008)
Evolution is present in world dynamics. And it is just in such transformational environment where companies have been encapsulated. In an economy of knowledge, physical assets alone are unable to provide profits to meet shareholders' demands. Now there comes an invisible component with the purpose of defining strategies and impelling results: Intangible Assets. Banking financing systems, however, have not kept pace with this knowledge revolution and its resulting new income generation techniques. Credit analysis methods for most financing agents would not employ any intangible parameters in their methodology of study as yet. This paper seeks to discuss the importance of intangible assets by focusing their role of influencial factor in decisions to finance technology-based companies. By studying the credit risk classification system employed by FINEP, Brazil's Federal Agency for innovation development, we wished to suggest indicators for intangibles which might be put to use in the Financiadora.